The blue shoe : a tale of thievery, villainy, sorcery, and shoes - Townley, Rod (Alfred A. Knopf, 2009)
A mysterious stranger commissions a single, valuable shoe from a humble cobbler, changing the cobbler's life and the life of his young apprentice forever.